Hubungan Antara Iklim Sekolah dan Stres Guru - Yusnida, Md Yusof (2009)
The main purpose of the study is to examine the relationship between school climate and stress among teacher in primary school at Perlis. Out of 92 samples from 254 subordinates were selected by using simple and stratified random system (SRS) as a sample in this study however only 58.3% only returned and accepted for the analysis. The teachers were selected from 10 schools of two different areas, town of Kangar and rural areas around Perlis. In this study, school climate has been measured using instrument that was developed by Pashiardis (2000). It consists four (4) dimensions; communication (9 items), Cooperation (7 items), Organization & Administration (8 items), Student (6 items) with 5-Llikert scale starting from 1 for totally disagree to 5 for totally agree. The concept of stress has been measured using 5 item instruments that were adapted by Conley (2000) with 5-Likert scale starting from 1 for never to 5 for always. The findings showed that there were high level of school climate and also high level of stress among teachers. The regression analysis also showed that by overall school climate does not have any significant effect on stress although one of its dimensions had. So, the research was unable to confirm any evidence on school climate effect toward stress. The research also founds that there was no significant difference between stress and demographics factors.